2020
DOI: 10.3390/pathogens9050362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance Profiles, Virulence and Enterotoxins-Determinant Genes of MRSA Isolated from Subclinical Bovine Mastitis in Egypt

Abstract: Subclinical mastitis caused by Staphylococcus aureus has worldwide public health significance. Here, we aimed to determine the prevalence of S. aureus, antimicrobial resistance profiles, and the virulence and enterotoxins determinant genes of MRSA strains that caused subclinical bovine mastitis. Milk samples were collected from 120 lactating animals (50 buffaloes and 70 dairy cattle) from different farms located in Ismailia Province (Egypt). The collected samples were investigated for subclinical mastitis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 44 publications
9
59
6
1
Order By: Relevance
“…Globally, several antimicrobial agents are frequently used for the treatment and/ or prevention of fish bacterial diseases. The indiscriminate use of antibiotics, as well as the emerging antibiotic resistance genes, could result in the occurrence of multi-drug resistant (MDR) strains [47][48][49][50] . Therefore, the routine application of antibiotic sensitivity testing is significant to select the specifically effective antibiotic and overcome such a problem [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…Globally, several antimicrobial agents are frequently used for the treatment and/ or prevention of fish bacterial diseases. The indiscriminate use of antibiotics, as well as the emerging antibiotic resistance genes, could result in the occurrence of multi-drug resistant (MDR) strains [47][48][49][50] . Therefore, the routine application of antibiotic sensitivity testing is significant to select the specifically effective antibiotic and overcome such a problem [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…55 S. aureus is one of the important occasions of subclinical and clinical bovine mastitis in Egypt. Algammal et al, 56 reported that the prevalence of S. aureus in subclinical bovine mastitis was 35.9%; out of them 35.7% were MRSA strains. PCR revealed that the isolated strains are positive for enterotoxin A (30%) and enterotoxin C (10%) genes.…”
Section: Staphylococcal Hyaluronidasementioning
confidence: 99%
“…The high prevalence of MRSA in raw milk of clinically healthy animals is of a great public health concern since the virulent MRSA strains could be transmitted to the human consumers causing serious illness and food poisoning. 56 Fish is considered a major source of animal protein with high nutritive value and a better conversion rate. [58][59][60] Staphylococci are not a normal fish microbiota; however, their presence could indicate post-harvest contamination due to bad personal hygiene, or fish disease.…”
Section: Staphylococcal Hyaluronidasementioning
confidence: 99%
“…The multidrug-resistance was observed among the majority of the isolated S. aureus, P. multocida and P. aeruginosa strains against 3-4 antimicrobial agents, while most of E. coli strains were resistant to 4 antimicrobial agents, and could be attributed to the random use of antibiotics over time in animal production (Haftu et al 2012) and of clinical significance, particularly in the calves industry system. Previous studies from Ethiopia, Brazil, Belgium, Egypt, and Canada have indicated that there is a remarkable increase in the prevalence of multidrugresistant E. coli, S. aureus and P. multocida strains (Catry et al 2016;Eid et al 2019;Enany et al 2019;Haftu et al 2012;Timsit et al 2017, Algammal et al 2020.…”
Section: Discussionmentioning
confidence: 99%